2011
DOI: 10.1007/s11882-011-0239-y
|View full text |Cite
|
Sign up to set email alerts
|

Management of Multiple Drug Allergies in Children

Abstract: Children with multiple drug allergies are likely to require treatment with one or more of the drugs to which they may have had a reaction, when there is no alternate effective drug available. Detailed review of their history and/or use of appropriate diagnostic studies will help determine the potential safety of readministering the desired drug as well as the method for its readministration, most likely in the form of a drug challenge or desensitization. A practical approach to the diagnosis and treatment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…A minority are dose independent, including antibody-and IgE-mediated reactions. 52,53,55,56 The off-target mechanism of non-IgE-mediated mast cell activation for many drugs (such as opiates, neuromuscular blocking agents, fluoroquinolones, and potentially vancomycin) entails the dose-dependent activation of a specific mas-related G proteincoupled receptor on mast cells. 57,58 Red man syndrome because of non-IgE-mediated mast cell activation secondary to vancomycin administration is a clinical example of a type B reaction in children.…”
Section: Classification Of Adrsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minority are dose independent, including antibody-and IgE-mediated reactions. 52,53,55,56 The off-target mechanism of non-IgE-mediated mast cell activation for many drugs (such as opiates, neuromuscular blocking agents, fluoroquinolones, and potentially vancomycin) entails the dose-dependent activation of a specific mas-related G proteincoupled receptor on mast cells. 57,58 Red man syndrome because of non-IgE-mediated mast cell activation secondary to vancomycin administration is a clinical example of a type B reaction in children.…”
Section: Classification Of Adrsmentioning
confidence: 99%
“…The provider should determine if treatment was required for the reaction as well as the response to treatment. 32,55,102,103 If a provider is suspicious that an IgE-mediated allergic reaction occurred (Table 1), workup should be considered (Fig 6). Immediate reactions that typically occur within 1 hour of exposure to oral drugs or within 15 to 20 minutes for parenteral drugs should prompt referral to an allergist for further workup.…”
Section: Figurementioning
confidence: 99%
“…Considering that cutaneous adverse drug reactions in our patients were associated with delayed hypersensitivity, the protocol should be referred to as the 'induction of tolerance' rather than 'desensitization.' However, at present 'desensitization' is used when referring to various non-IgE-mediated hypersensitivity reactions, because the pathomechanism of desensitization is not fully understood and nonimmunologic mechanisms are thought to be involved 927. In addition, numerous studies have found successful desensitization to non-IgE-mediated reactions, such as those involving sulfonamide, temozolomide, and allopurinol, and in doing so reflect the extended meaning of desensitization 282930.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true in the setting of latent tuberculosis where treatment options are limited. Desensitization induces a temporary state of tolerance to a medication that has provoked a hypersensitivity response by administering incremental doses of the medication until the total cumulative therapeutic dose is achieved (2). This tolerance can be maintained as long as the medication is administered at regular intervals without discontinuation or missed doses (3).…”
mentioning
confidence: 99%
“…As patients with CGD are at increased risk for invasive bacterial and fungal infections, conservative therapy is based on the lifelong prophylactic use of cotrimoxazole and itraconazole. The latter substantially lowers the incidence of invasive aspergillosis and thus significantly improved long-term outcome in CGD in terms of morbidity and mortality (2). However, multiple drug interactions of itraconazole must be considered as itraconazole raises levels of calcineurin inhibitors (tacrolimus, cyclosporine A), while rifampicin lowers levels of itraconazole (3).…”
mentioning
confidence: 99%